The association of aldosterone and endothelin-1 with incident diabetes among African Americans: The Jackson Heart Study - Joshua J. Joseph; Bjorn Kluwe; Songzhu Zhao; David Kline; Divya Nedungadi; Guy Brock; Willa A. Hsueh; Sherita H. Golden (Endocrine and Metabolic Science, 2023)
Introduction: African Americans (AAs) have the highest prevalence of hypertension among United States racial/ethnic groups. Regulators of blood pressure, such as aldosterone and endothelin-1, impact glucose regulation. The relationship between these factors and incident diabetes is not well elucidated among AAs. Methods: Among 3914 AA participants without prevalent diabetes in the Jackson Heart Study, linear regression models were used to examine cross-sectional associations of exposures (aldosterone, endothelin-1, and a combined aldosterone-endothelin-1 score [2–8]) with glycemic measures (fasting plasma glucose [FPG], HbA1c, homeostatic model assessments of beta cell function [HOMA-β] and insulin resistance [HOMA-IR]). Longitudinal associations of exposures with incident diabetes were examined using Cox proportional hazard models. Models were adjusted for age, sex, education, occupation, systolic blood pressure, smoking, physical activity, dietary intake, alcohol use and adiponectin. Results: Aldosterone and the combined aldosterone-endothelin score were positively associated with FPG, HOMA-IR, and HOMA-β (all p < 0.05). Endothelin-1 was negatively associated with FPG but positively associated with HOMA-β (both p < 0.05). Only the aldosterone-endothelin score was positively associated with HbA1c (p < 0.01). A 1-SD higher serum aldosterone and endothelin-1 was associated with a 22 % and 14 % higher risk of incident diabetes, respectively, while a 1-point higher aldosterone-endothelin score was associated with a 13 % higher risk of incident diabetes after adjustment for diabetes risk factors (all p < 0.01). Conclusions: Aldosterone and endothelin-1, factors integral in blood pressure regulation, may play a significant role in the development of diabetes among AAs.